Defect‐Concentration‐Mediated T‐Nb2O5 Anodes for Durable and Fast‐Charging Li‐Ion Batteries. (30th November 2021) - Zheng, Yongjian; Yao, Zhenguo; Shadike, Zulipiya; Lei, Meng; Liu, Jianjun; Li, Chilin
Abstract: Metastable orthorhombic niobium pentoxide (T‐Nb2 O5 ) is a promising anode to fulfill the requirements for high‐rate Li‐ion batteries (LIBs). Stoichiometric T‐Nb2 O5 is plagued by low electric conductivity and particle pulverization after repeated charge/discharge processes. In this work, oxygen vacancies are implanted into T‐Nb2 O5 particles via acid immersion of Nb2 O5 · n H2 O with the formation of Lewis acid sites. The multiple characterizations and simulations reveal the lengthening of NbO bonds, and the transformation from NbO7 pentagonal bipyramids and NbO6 tetragonal bipyramids in T‐Nb2 O5− x . The enrichment of oxygen vacancies endows T‐Nb2 O5− x with higher electric conductivity, better electrochemical kinetics, larger pseudocapacitive contribution. O‐doped graphitic C3 N4 is creatively proposed as a trace oxygen pump to repair excessive oxygen vacancies, and it also serves as a sacrifice template for Nb2 O5− x growth to construct a porous and monolithic electrode network. Defect‐modulated Nb2 O5− x displays extraordinary cycling stability (164 mAh g −1 at 5 C after 1100 cycles), high capacity retention (104 mAh g −1 ) at an ultrahigh rate (25 C), and large areal capacity (0.74 mAh cm −2 ) under high mass loading (4 mg cm −2 ). The practical prospect is proved by Nb2 O5− x /LiNi0.8 Co0.1 Mn0.1 O2 full cells with high average platform (2.12 V) and high specific capacity (229 mAh g −1 ). The oxygen‐defect modulation strategy on oxide anodes provides an alternative solution to fast‐charging and durable LIBs. Abstract : Oxygen vacancies are implanted into orthorhombic niobium pentoxide (T‐Nb2 O5 ) particles via acid immersion of Nb2 O5 · n H2 O with the formation of Lewis acid sites. The enrichment of oxygen vacancies endows T‐Nb2 O5− x with much higher electric conductivity, better electrochemical kinetics, larger pseudocapacitive contribution. O‐doped graphitic C3 N4 is creatively proposed as trace oxygen pump to repair excessive oxygen vacancies.